Shallow gas detection and data transmission in the formation. Issue 5 (February 2020) - Zheng, Junjie; Jia, Shengyao; Li, Qing
Abstract: In recent years, with the proposal and implementation of national marine strategy, more and more marine engineering facilities are being developed. All marine engineering construction is bound to be inseparable from marine geological survey, and the existence of shallow gas in the stratum is also a big invisible danger in the engineering. Therefore, this study used waterproof and breathable film to separate the shallow layer of gas, then measured the methane concentration with infrared methane gas sensor and sent the formation information measured by CPTU probe the data acquisition module through the electromagnetic wave wireless module. Finally, all measured values are transmitted to the ground via a cable.